Evaluación de la floculación en el proceso de remoción del colorante Azoico Rojo Congo empleando un coagulante orgánico extraído de la pulpa de café (2024)
The textile dyeing industry consumes large amounts of water and produces significant volumes of wastewater resulting from the various dyeing and finishing processes. The main objective of this study is to evaluate the effectiveness of the coagulation-flocculation process using a natural coagulant obtained from polyphenolic compounds by ultrasound-assisted extraction. By evaluating the conditions of temperature, solid-liquid ratio and time, a maximum concentration of polyphenolic compounds of 8.77 mgGAE/gBS was achieved. The results showed high removal percentages of the Congo Red dye, especially with the use of polyaluminium chloride as a flocculant, reaching up to 97.22% removal at pH 2. These findings are promising compared to the use of conventional coagulants such as aluminium sulphate, suggesting a potential positive impact on the wastewater treatment industry.